Thermal preparation and characterization of nanodispersed copper-containing powders produced by non-equilibrium electrochemical oxidation of metals; Solid State Sciences; Vol. 108 - Korobochkin V. V. Valery Vasilievich; Potgieter J. H. Johannes Herman; Usoltseva N. V. Natalia Vasilievna; Dolinina A. S. Alesya Sergeevna; An V. V. Vladimir Vilorievich (2020, 2020)
Title screen